Hyaluronic acid engrafted metformin loaded graphene oxide nanoparticle as CD44 targeted anti-cancer therapy for triple negative breast cancer - Basu, Arijita; Upadhyay, Priyanka; Ghosh, Avijit; Bose, Aparajita; Gupta, Payal; Chattopadhyay, Sreya; Chattopadhyay, Dipankar; Adhikary, Arghya (Biochimica et biophysica acta. General subjects, 2021)
Triple negative breast cancer (TNBC) is the most aggressive form of breast cancer with limited treatment modalities. It is associated with high propensity of cancer recurrence. UV Spectroscopy, FTIR, DLS, Zeta potential, TEM and SEM were employed to characterize nanoparticles. MTT assay, Wound healing assay, SEM, Immunocytochemistry analysis, Western blot, RT-PCR, mammosphere formation assay were employed to study apoptosis, cell migration and stemness. Tumor regression was studied in chick embryo xenograft and BALB/c mice model. Hylaluronic acid engrafted metformin loaded graphene oxide (HA-GO-Met) nanoparticles exhibited an anti-cancer efficacy at much lower dosage as compared to metformin alone. HA-GO-Met nanoparticles induced apoptosis and inhibited cell migration of TNBC cells by targeting miR-10b/PTEN axis via NFkB-p65. Upregulation of PTEN affected pAKT(473) expression that induced apoptosis. Cell migration was inhibited by reduction of pFAK/integrinβ1 expressions. Treatment inhibited epithelial mesenchymal transition (EMT) and reduced stemness as evident from the increase in E-cadherin expression, inhibition of mammosphere formation and low expression levels of stemness markers including nanog, oct4 and sox2 as compared to control. Moreover, tumor regression was studied in chick embryo xenograft and BALB/c mice model. HA-GO-Met nanoparticle treatment reduced tumor load and nullified toxicity in peripheral organs imparted by tumor. HA-GO-Met nanoparticles exhibited an enormous anti-cancer efficacy in TNBC in vitro and in vivo. HA-GO-Met nanoparticles induced apoptosis and attenuated cell migration in TNBC. It nullified overall toxicity imparted by tumor load. It inhibited EMT and reduced stemness and thereby addressed the issue of cancer recurrence. [Display omitted] •HA-GO-Met nanoparticles selectively targeting CD44+ TNBC cells.•It targets miR10b axis via NFķB-p65.•It induces apoptosis via PTEN and inhibits cell migration via integrinβ1/pFAK.•It inhibits epithelial-mesenchymal transition by targeting miR10b.•HA-GO-Met nanoparticles exhibit excellent therapeutic efficacy in vitro and in vivo.